2018
DOI: 10.1002/dc.23907
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cytological findings from the use of the Integran microfibrillar collagen hemostatic matrix in conization

Abstract: The Integran microfibrillar collagen hemostatic matrix is one form of microfibrillar collagen hemostat. This form has a sheet-type structure and has explicitly been used in Japan. In gynecology, this sheet-type matrix has helped effect uterine surface hemostasis, especially in myomectomy and cervical conization. However, cytotechnologists and pathologists have overlooked the foreign materials used for conization in postoperative cervical cytology. We report two cases describing the characteristic cervical cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Very few cases mentioning cytology have been previously reported in the medical literature, and there have been only 2 concerning the use of oxidized cellulose . Two other cases are related to the use of other hemostatic agents (Floseal and Integran microfibrillar collagen hemostatic matrix) that do not use oxidized cellulose but instead use thrombin and collagen …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very few cases mentioning cytology have been previously reported in the medical literature, and there have been only 2 concerning the use of oxidized cellulose . Two other cases are related to the use of other hemostatic agents (Floseal and Integran microfibrillar collagen hemostatic matrix) that do not use oxidized cellulose but instead use thrombin and collagen …”
Section: Discussionmentioning
confidence: 99%
“…11,12 Two other cases are related to the use of other hemostatic agents (Floseal and Integran microfibrillar collagen hemostatic matrix) that do not use oxidized cellulose but instead use thrombin and collagen. 13,14 The cytologic image is so characteristic that the diagnosis is straightforward with few differential diagnostic considerations. Half of the cases had no significant granulomatous reaction, and smears showed only oxidized cellulose material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytology has demonstrated that it is capable of a speci c recognition of pseudotumoral reactions induced by oxidized cellulose (1)(2)(3)(4). Cases that simulate tumor recurrence have been described after almost all types of surgical procedures in which this hemostatic agent has been used.…”
Section: Declarationsmentioning
confidence: 99%